Evaluation of electrocoagulation by Fenton reagent for the removal of turbidity and sulfides in wastewater from the process of depilation or liming in the tanneries - Robayo Triana, Oscar Enrique; Sánchez Pérez, Diego Alberto; Rafael Nikolay , Rafael Nikolay (Ingeniería Solidaria, 2020)
Introduction: This article is the result of the research "Evaluation of the intensified electrocoagulation in wastewater of the liming process in The Scorpion tannery in the municipality of Villapinzón-Cundinamarca with analysis at the Universidad Libre de Colombia-Sede Bosque Popular between 2018 and 2019. Objective: To evaluate the Electro-Fenton strategy as an alternative for the treatment of wastewater from the skin tanning process. Methodology: An experimental design of factorial type 33 is used in two phases, utilizing a Batch type reactor, in the first phase the number of iron electrodes, H2O2 dosage and current intensity supplied is analyzed. For the second phase, the reaction time is varied, with a number of plates defined the parameters of sulfide concentration, total organic carbon (TOC) and both initial and final turbidity for a subsequent analysis of variance (ANOVA) were analyzed. Conclusion: In the first stage of treatment for a reaction time of 60 minutes a turbidity removal of 96.2%, 65.4% sulfide and 52.3% of TOC was obtained, with these it was determined that with 4 electrodes the greatest removal was obtained. In the second stage with follow-up treatment in function of time, a removal of 99.2% for turbidity, 68.35% for sulfur and 53.5% for TOC was obtained. Originality: An electrochemical system is used to treat wastewater from the tannery industry, based on previous research, in order to adapt the technology to the sector mentioned initially. Limitations: The study is limited to the use of iron electrodes, current densities and doses of H2O2 used, in this type of systems aluminum electrodes, stainless steel, graphite and doped materials can be used to maximize the reaction in the electrodes, as well as the use of ozone as an oxidizing agent.